2023
DOI: 10.1038/s41467-023-42419-8
|View full text |Cite
|
Sign up to set email alerts
|

Months-long seismicity transients preceding the 2023 MW 7.8 Kahramanmaraş earthquake, Türkiye

G. Kwiatek,
P. Martínez-Garzón,
D. Becker
et al.

Abstract: Short term prediction of earthquake magnitude, time, and location is currently not possible. In some cases, however, documented observations have been retrospectively considered as precursory. Here we present seismicity transients starting approx. 8 months before the 2023 MW 7.8 Kahramanmaraş earthquake on the East Anatolian Fault Zone. Seismicity is composed of isolated spatio-temporal clusters within 65 km of future epicentre, displaying non-Poissonian inter-event time statistics, magnitude correlations and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Various large earthquakes were observed to be preceded by precursory deformation and foreshock seismicity on varying scales in space and time, but the observed patterns are diverse and do not always occur (e.g., Kanamori, 1981; Kato & Ben‐Zion, 2021; Kwiatek et al., 2023; Sykes, 2021; Wu et al., 2013). Recent studies of laboratory data showed that the use of AI techniques and features derived from AEs can open up new avenues toward forecasting laboratory earthquakes on smooth faults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various large earthquakes were observed to be preceded by precursory deformation and foreshock seismicity on varying scales in space and time, but the observed patterns are diverse and do not always occur (e.g., Kanamori, 1981; Kato & Ben‐Zion, 2021; Kwiatek et al., 2023; Sykes, 2021; Wu et al., 2013). Recent studies of laboratory data showed that the use of AI techniques and features derived from AEs can open up new avenues toward forecasting laboratory earthquakes on smooth faults.…”
Section: Discussionmentioning
confidence: 99%
“…Faults evolve with progressive loading over geological timescales, displaying a qualitatively comparable evolution of many parameters (e.g., localization, b ‐value) regardless of their structural and mechanical complexity (Ben‐Zion & Sammis, 2003; Tchalenko, 1970). However, it is feasible to observe very different precursory signatures, depending on fault structure (roughness, complexity) and other conditions (Ellsworth & Bulut, 2018; Huang et al., 2020; Kato & Ben‐Zion, 2021; Kwiatek et al., 2023). For rough faults, our study suggests that a combination of physics‐based parameters, reinforced with ML techniques, can indicate when the system is entering a critical stage.…”
Section: Potential Applications To Earthquake Forecastingmentioning
confidence: 99%
See 1 more Smart Citation